A PV based automation system for fish farms: An application study - Bayrak, Gökay; Lebeli, Menmet (My University, 2011)
Nowadays, generating electricity from solar energy is used for many applications. Especially in rural areas, PV based applications have been a great importance for generating electricity. In this study, a PV based application study presented for fish farms. An off grid PV system designed to supply the systems' required electrical energy and a pump used for taking cold water from the depth of the dam lake to cool the cage. Temperature sensors are used for measuring the cage's water temperature and according to the cage temperature a motor driver is used to adjust the speed of pump. A PLC controller and an HMI system for monitoring designed for the system. All the energy requirement of the system is supplied from designed PV system. Thanks to developed system, the temperature of fish cage is stabilized to 17°C so from May to September, fish can be growth sustainably during the year. © 2011 Chamber of Turkish Electric.
7th International Conference on Electrical and Electronics Engineering, ELECO 2011 -- 1 December 2011 through 4 December 2011 -- Bursa -- 88625
Keywords: Electronics engineering; Fish; Monitoring; Photovoltaic effects; Rural areas; Systems analysis; Application studies; Automation systems; Cold waters; Electrical energy; Energy requirements; Fish cages; Fish farms; Motor driver; Off-grids; PV system; Water temperatures; Electric generators